Analisa Faktor - Faktor Pendukung Kinerja Sales Asuransi Melalui Kepuasan Kerja Sebagai Mediasi - Christini, Julia; Fatyandri, Adi Neka (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This study aims to investigate the impact of training, job development, compensation, and work motivation on employee performance, with job satisfaction as a mediating variable among insurance sales employees in Batam. Using a sample of 310 respondents obtained through the distribution of Google Form questionnaires to insurance employees in Batam, this research employed data processing with Smart PLS 3.0 software. The study found that Training has a positive impact on job satisfaction, while career development does not significantly affect job satisfaction. Competence has been proven to have a positive impact on job satisfaction, while motivation does not significantly influence job satisfaction. Training also contributes positively to employee performance through job satisfaction, while career development does not significantly affect employee performance mediated by job satisfaction. Competence shows a positive impact on employee performance with job satisfaction as a mediation, while motivation does not significantly influence employee performance mediated by job satisfaction.